7(x-2)-4(x+1)=-21

Simple and best practice solution for 7(x-2)-4(x+1)=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-2)-4(x+1)=-21 equation:


Simplifying
7(x + -2) + -4(x + 1) = -21

Reorder the terms:
7(-2 + x) + -4(x + 1) = -21
(-2 * 7 + x * 7) + -4(x + 1) = -21
(-14 + 7x) + -4(x + 1) = -21

Reorder the terms:
-14 + 7x + -4(1 + x) = -21
-14 + 7x + (1 * -4 + x * -4) = -21
-14 + 7x + (-4 + -4x) = -21

Reorder the terms:
-14 + -4 + 7x + -4x = -21

Combine like terms: -14 + -4 = -18
-18 + 7x + -4x = -21

Combine like terms: 7x + -4x = 3x
-18 + 3x = -21

Solving
-18 + 3x = -21

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 3x = -21 + 18

Combine like terms: -18 + 18 = 0
0 + 3x = -21 + 18
3x = -21 + 18

Combine like terms: -21 + 18 = -3
3x = -3

Divide each side by '3'.
x = -1

Simplifying
x = -1

See similar equations:

| 6(2x-2)=45+5x | | 9y+3016+6y=13y-2y | | (v-2w-2)(v-4)=0 | | 2=200/w^2 | | 2x+8+x+1=0 | | 3(20x+50)=510 | | 5x+24(x-2)=184 | | -5x+40=6x-(70) | | 40x+7=40d+34 | | (27x^4)+3p=2p | | 2m+3=2m-3 | | 6r^3+2r^2-48r= | | 3y-7=80 | | H-3=12 | | (3v-w-2)(7v+6)=0 | | 4(x+2)+3(x-6)=-3 | | 5x-20=x-2.4 | | 5a/24÷1/12 | | 9x/-102/3 | | -5t=-35 | | ln[(x-9)/((x^(2)-81)^(5))]^((2)/(5)) | | (3x+21)=(6x+15) | | 7p+21+9=10p-10-3p | | X^4-5x^2=-6 | | 2x^2+4x=240 | | 3x+5y=102 | | X+25+3(x)=435 | | 4(x-5)=-1.2x-1.2 | | (2x+4)2=240 | | D-4/9=-1/12 | | 85-x=20+x | | 5x(200)+10x=1630 |

Equations solver categories